2012
DOI: 10.1016/j.pmrj.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Power and Muscle Strength in Human Immunodeficiency Virus–Positive Preadolescents

Abstract: Objective To determine the anaerobic power and muscle strength of preadolescents with human immunodeficiency virus (HIV). Design Cross-sectional design. Setting Human performance laboratory at the University District Hospital at the Puerto Rico Medical Center. Participants Fifteen preadolescents (8 girls and 7 boys) with a classification of HIV A and B attending an investigational treatment program at the University Pediatric Hospital. Fifteen seronegative control subjects matched by age and gender also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Furthermore, neither muscle mass nor function was associated with bone density, suggesting that muscle is not affected in the same way as bone in the context of longstanding paediatric HIV infection. A small study of 15 Puerto Rican CWH also found CWH to have similar lower limb muscle strength to uninfected controls [33]. Although, a more recent Canadian study which assessed lower limb muscle function by jumping mechanography, in a population 2 years older than ours (n = 35), did find an albeit small difference in lower limb muscle power [13].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, neither muscle mass nor function was associated with bone density, suggesting that muscle is not affected in the same way as bone in the context of longstanding paediatric HIV infection. A small study of 15 Puerto Rican CWH also found CWH to have similar lower limb muscle strength to uninfected controls [33]. Although, a more recent Canadian study which assessed lower limb muscle function by jumping mechanography, in a population 2 years older than ours (n = 35), did find an albeit small difference in lower limb muscle power [13].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, neither muscle mass or function were associated with bone density, suggesting that muscle is not affected in the same way as bone in the context of longstanding paediatric HIV infection. A small study of 15 Puerto Rican CWH were also found to have similar lower limb muscle strength to uninfected controls 33 . Although, a more recent Canadian study which assessed lower limb muscle function by jumping mechanography, in a population 2 years older than ours (n=35), did find an albeit small difference in lower limb muscle power 13 .…”
Section: Discussionmentioning
confidence: 93%
“…Muscle strength was evaluated in only two studies [ 6 , 26 ], in which one study used the maximum repetition evaluation test, while the other study used the isokinetic strength test to quantify lower limb muscle strength. The studies that evaluated strength had a total of 111 participants (60 with HIV and 51 healthy controls).…”
Section: Resultsmentioning
confidence: 99%
“…Body composition was assessed in four of the five included studies. Of these, three used the anthropometric method and only one study used the DXA method, which is the gold standard for this evaluation [ 6 , 11 , 26 , 28 ]. The studies included 382 participants (197 infected with HIV and 185 healthy controls).…”
Section: Resultsmentioning
confidence: 99%